SUN-700 Fournier’s Gangrene and Diabetic Ketoacidosis Caused by Canagliflozin - Stamatiades, George Alexiades (J Endocr Soc, 2020)
Introduction Sodium glucose co-transporter 2 (SGLT2) inhibitors have become an appealing treatment for diabetes due to their favorable cardiac and renal outcomes. However, reports continue to emerge describing potentially life-threatening adverse events such as Fournier’s gangrene (FG) and diabetic ketoacidosis (DKA) associated with their use. Herein, we report a case of simultaneous FG and DKA in a patient taking canagliflozin. Case Presentation A 37-year-old woman with a history of type 2 diabetes mellitus, peripheral neuropathy, and morbid obesity (BMI of 45.8 kg/m(2)) presented to the hospital with left gluteal pain associated with dysuria despite 5-day treatment with trimethoprim/sulfamethoxazole for a presumed urinary tract infection. Approximately 1 month prior, sitagliptin and canagliflozin were added to her regimen due to poor glycemic control on metformin (HbA1c 9.8%). On examination her temperature was 36.9(o)C, pulse 117 beats/minute, blood pressure 144/79 mmHg and respiratory rate was 19 bpm. She appeared lethargic and had suprapubic tenderness and induration in the left gluteal region extending to the perineum. Laboratory findings revealed an arterial pH of 7.23 and PCO2 of 34 mmHg, a blood glucose of 402 mg/dL, serum bicarbonate 12mmol/L (20-30mmol/L), an elevated anion gap of 24mmol/L (7-17mmol/L) and a lactate of 1.8 mmol/L. Urinalysis showed 4+ glucose and 1+ ketones. Serum β-hydroxybutyrate was 2.49 mmol/L (0.02-0.27mmol/L). A CT scan of the abdomen and pelvis showed marked inflammatory changes with subcutaneous edema and air within the medial left gluteal soft tissues and locules of air extending into the presacral soft tissues suggestive of Fournier’s gangrene. The diagnoses of Fournier’s gangrene and DKA were made. The patient was started on empirical antibiotic treatment and required six surgical explorations with debridement. Interestingly, initial DKA management included only subcutaneous insulin. Only when serum ketones were identified and the anion gap persisted, insulin infusion with aggressive fluid resuscitation was initiated with successful resolution of anion gap metabolic acidosis. She was discharged with a urinary catheter, vacuum dressing, colostomy with instructions to start insulin glargine 18U and discontinue the oral anti-diabetic medications. Discussion To the best of our knowledge, this is the first case describing the simultaneous occurrence of two potentially fatal adverse effects of SGLT2 inhibitor therapy; Fournier’s gangrene and DKA. In light of the FDA’s warnings and the growing popularity of SGLT2 inhibitor therapy it is important to be mindful of their more serious and potentially fatal complications. It is also important to promptly terminate SGLT2 inhibitors when harmful adverse effects are suspected to prevent further progression.